Pengaruh Stres Kerja dan Pengembangan Karir Terhadap Prestasi Kerja Karyawan Pada PT. Jasa Marga (Persero) Tbk Cabang Belmera - Mohd. Heikal (Faculty of Economics and Business, Universitas Malikussaleh, 2016)
Job performance is as a result of work has been accomplished person from his behavior in carrying out work activities. There are several factors that affect the achievement of which stress and career development. Stress may contribute incorrectly or damaging the work performance. In simple terms this means that the stress potential to disrupt the implementation of the work. In addition to job stress, career development is also a matter that affects job performance. Career development needsto be done in a planned and sustainable. With the opening of the career opportunities are accompanied by a realistic career goals and reasonable could lead to a satisfactory performance. Both of these need to be considered by PT. Jasa Marga (Persero)Tbk Branch Belmera in terms of improving performance. This study aimed to determine the effect of work stress on work performance, to determine the effect of job stress and career development to job performance. Data collection techniques in this study using a study of documentation, interviews and using a questionnaire. The processed data was analyzed qualitatively and quantitatively.Keywords: Job Stress, Career Development, Job Performance